Electrical isolation of the left atrial appendage by Maze‐like catheter substrate modification: A reproducible strategy for pulmonary vein isolation nonresponders?. (26th July 2017) - Bordignon, Stefano; Perrotta, Laura; Dugo, Daniela; Bologna, Fabrizio; Nagase, Takahiko; Fuernkranz, Alexander; Chun, K.R. Julian; Schmidt, Boris
Abstract: Introduction: The ablation strategy for atrial fibrillation (AF) despite pulmonary vein isolation (PVI) is controversial. Left atrial appendage isolation (LAAI) may contribute to improve outcome. We describe an ablation approach ("Maze‐like"‐LAAI) that (1) modifies the underlying LA substrate by linear ablation (2) eliminates the LAA as a putative AF trigger site and (3) incorporates an unambiguous procedural endpoint. The role of LAA closure (LAAC) after LAAI was investigated. Methods: Patients with atrial tachyarrhythmias nonresponsive to PVI underwent a LAAI ablation procedure. LAAI was achieved by combining (a) an anterior line, (b) a LA roof line and (c) a mitral isthmus line. Patients continued oral anticoagulation (OAC) therapy or underwent LAAC ≥6 weeks after LAAI. Results: Maze‐like LAAI was attempted in our center in 107 of 3, 611 AF ablation procedures (2.9%) and achieved in 88 of 107 patients (82%). In 8 of 107 (7%) patients cardiac tamponade occurred, all managed conservatively. During follow‐up sinus rhythm was established in 65% at 1 year. After LAAI, 45 patients remained on OAC and 40 underwent LAAC. In both groups 1 patient experienced a bleeding complication. Thromboembolism exclusively occurred in the OAC group in 3 (7%) patients. Conclusion: LAA isolation by Maze‐like substrate modification may be considered a viable option for PVI non‐responders. It offers a reproducible approach with an unambiguous procedural endpoint and leads to a favorable clinical outcome. However, extensive LA ablation increased the risk of tamponade. Consecutive LAA occlusion may offer a nonpharmacologic strategy to overcome the high thromboembolic risk associated with absent mechanical LAA contraction.